Not Oligomers but Amyloids are Cytotoxic in the Membrane‐Mediated Amyloidogenesis of Amyloid‐β Peptides. (19th January 2018) - Itoh, Naoya; Takada, Eri; Okubo, Kaori; Yano, Yoshiaki; Hoshino, Masaru; Sasaki, Akira; Kinjo, Masataka; Matsuzaki, Katsumi
Abstract: The formation of neurotoxic aggregates by amyloid‐β peptide (Aβ) is considered to be a key step in the onset of Alzheimer's disease. It is widely accepted that oligomers are more neurotoxic than amyloid fibrils in the aqueous‐phase aggregation of Aβ. Membrane‐mediated amyloidogenesis is also relevant to the pathology, although the relationship between the aggregate size and cytotoxicity has remained elusive. Here, aggregation processes of Aβ on living cells and cytotoxic events were monitored by fluorescence techniques. Aβ formed amyloids after forming oligomers composed of ≈10 Aβ molecules. The formation of amyloids was necessary to activate apoptotic caspase‐3 and reduce the ability of the cell to proliferate; this indicated that amyloid formation is a key event in Aβ‐induced cytotoxicity. Abstract : What's your poison? The aggregation processes of Aβ(1–42) on cells and cytotoxic events were investigated. Aβ formed amyloids after forming nontoxic oligomers composed of ≈ten Aβ molecules. The formation of amyloids was necessary to induce apoptosis and reduce the ability of the cell to proliferate; this indicates that amyloid formation is a key event in Aβ‐induced cytotoxicity.